Regional Economic Disparities in Australia - Ramakrishnan, Uma (IMF Working Papers; Working Paper ;, 2004)
Australia's remarkable economic performance during the 1990s has not resulted in a significant convergence of real per capita income, output, and employment levels across the country's states and territories. This paper explores the role of certain economic rigidities that may have contributed to the lack of convergence, including rigidities in labor markets and in the structure of federal government transfers to households and subnational governments. The analysis suggests that the wage awards system has restricted the adjustment of real wages to productivity differentials, thus contributing to higher unemployment rates in some states. Federal government transfers to households also appear to have adversely affected work incentives in high unemployment states by limiting participation in the labor force.